Proses Pemberdayaan dalam Upaya Peningkatan Hasil Produksi Pertanian Kelompok Tani Sido Makmur Dua Desa Sidomulyo Muara Enim - Ani Khairani; Shomedran Shomedran (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
This study aims to determine the process of empowerment in an effort to increase agricultural production. This type of research is descriptive qualitative, using interviews, observation and documentation, the number of research subjects is five people. The results of the research are the planning stage of farmer group activities consisting of preparation, setting goals, sources of activity funds, counseling materials, time and place of implementation. Implementation begins with delivering material, preparing for planting, sowing seeds, planting and harvesting together. Evaluation begins with participating in all empowerment activities until they are completed. Even though the results of the rice agricultural production of the Sido Makmur Dua farmer group did not always increase, it still had an impact on meeting the basic needs of group members.